2016
DOI: 10.3906/sag-1504-120
|View full text |Cite
|
Sign up to set email alerts
|

Traditional practices of Konya women during pregnancy, birth, the postpartumperiod, and newborn care

Abstract: Background/aim: The purpose of the present study was to identify traditional practices and the extent to which they are practiced by mothers during pregnancy, birth, the postpartum period, and newborn care. Materials and methods:This study was conducted in the city center of Konya (Turkey). Data were collected through questionnaires completed by volunteers. The research sample comprised 450 mothers, all of whom had given birth to at least one live baby. The forms were completed during face-to-face interviews.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
0
11
0
7
Order By: Relevance
“…Some of the traditional practices identified in this study are similar to those in other cultures, like Turkey, Iran, and Ghana [5][6][7]. The traditional massage among the Ijaws is similar to the equally popular Maya abdominal massage which has been found to be efficacious [8].…”
Section: Discussionmentioning
confidence: 70%
“…Some of the traditional practices identified in this study are similar to those in other cultures, like Turkey, Iran, and Ghana [5][6][7]. The traditional massage among the Ijaws is similar to the equally popular Maya abdominal massage which has been found to be efficacious [8].…”
Section: Discussionmentioning
confidence: 70%
“…Okka B et al reported similar tradition to the tune of 72.2% of the mothers reported performing kırklama (making the forties) in Turkish families, a ceremony performed to celebrate the 40th day after a baby's birth. 7 Removal of baby's hair ceremony (jadula) was planned in 148 (74%) cases, while plan to stay with own mother after delivery36 (18%) cases. Avoidance of colostrum to baby was found in to baby 82 (41%) cases.…”
Section: Discussionmentioning
confidence: 99%
“…Türkiye Nüfus Sağlık Araştırmaları (TNSA) 2013 verilerine göre tüm Türkiye'de bu oran %50 olup, ülkemizin çeşitli bölgelerindeki çalışmalarda ise %9.9-%89 arasında değişmektedir (14,(20)(21)(22)(23)(24). Dünyanın farklı ülkelerinde ise bu konuyla ilgili farklı oranlar; 'Suudi Arabistan'da %11.4 , Brezilya'da %67.7 ve SriLanka'da %83.3' şeklinde bildirilmektedir (25) (26,10,17,15). Pakistan'da, Hindistan'da da sırasıyla %30.9 ve %73.6 oranında bebeklerin ilk emzirilmelerinin geciktirildiği bildirilmiştir (27,28).…”
Section: Bulgularunclassified